ANALISIS PERBEDAAN KINERJA KEUANGAN SEBELUM DAN MASA PANDEMI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2019 - 2020 - Sri Lestari Tindaon; Lailah Fujianti; Mira Munira (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2023)
This study aims to analyze differences in financial performance before and during the covid-19 pandemic in manufacturing companies listed on the Indonesia Stock Exchange in 2019 - 2020. The variables used to see the difference in financial performance are current ratio (CR), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Inventory Turnover (ITO), Total Asset Turnover (TATO), Return On Asset (ROA), and Return On Equity (ROE). Using quantitative methods by taking data on the company's financial statements from the Indonesia Stock Exchange in 2019 - 2020. To test hypotheses used parametic and non parametic tests namely Paired sample t-test and Wilcoxon signed rank. The results of the study with different tests showed that there was no significant difference in variable current ratio, debt to asset ratio, and debt to equity ratio. While variable inventory turnover, total asset turnover, return on asset and return on equity there are significant differences. Pandemic covid-19 is not too bad for manufacturing companies because all three sectors are still able to experience development and financial performance is still stable.